Thermo- and pH-Responsive Gelatin/Polyphenolic Tannin/Graphene Oxide Hydrogels for Efficient Methylene Blue Delivery - Oliveira, Ariel C. de (2021)
Gelatin (GE), amino-functionalized polyphenolic tannin derivative (TN), and graphene oxide (GO) were associated to yield thermo- and pH-responsive hydrogels for the first time. Durable hydrogel assemblies for drug delivery purposes were developed using the photosensitizer methylene blue (MB) as a drug model. The cooling GE/TN blends provide brittle physical assemblies. To overcome this disadvantage, different GO contents (between 0.31% and 1.02% wt/wt) were added to the GE/TN blend at 89.7/10.3 wt/wt. FTIR and RAMAN spectroscopy analyses characterized the materials, indicating GO presence in the hydrogels. Incorporation studies revealed a total MB (0.50 mg/mL) incorporation into the GE/TN-GO hydrogel matrices. Additionally, the proposed systems present a mechanical behavior similar to gel. The GO presence in the hydrogel matrices increased the elastic modulus from 516 to 1650 Pa. SEM revealed that hydrogels containing MB present higher porosity with interconnected pores. Dissolution and swelling degree studies revealed less stability of the GE/TN-GO-MB hydrogels in SGF medium (pH 1.2) than SIF (pH 6.8). The degradation increased in SIF with the GO content, making the polymeric matrices more hydrophilic. MB release studies revealed a process controlled by Fickian diffusion. Our results point out the pH-responsible behavior of mechanically reinforced GE/TN-GO-MB hydrogels for drug delivery systems purposes.